(untitled) (Altre Modernità, 2021)
With this article we tried to focus our reading upon the poems that compose Chilean writer Tomás Harris’ La vida a veces toma la forma de los muros (a section included in his 1992 work Cipango). After considering the texts depending on their order of appearance, we intended to identify those changes experienced by the image of the wall and its relation with the lyrical subjects. Actually, the evident relevance of the wall affects not only the work themes, but also the verbal form itslef. This proceeding approached us to a variety of impressions that could promote an existential perspective of wide reach, in addition to agreeing with other critical contributions. Thanks to the support of the thinking of authors like Deleuze, Guattari, and Sartre, among others, we realised that, starting from the wall element, a series of manifestations happens by questioning the notion of human perception and consciousness.